2021
DOI: 10.1155/2021/8866211
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Studies on the Inflatable Recyclable Anchor in the Tube Piece Type Based on the Soil‐Anchor Interaction Mechanism

Abstract: This paper deeply studies the characteristics and “uplift bearing capacity” of a novel type of inflatable recyclable anchor in the tube piece. The proposed novel inflatable recyclable anchor in the tube piece type comprises a metallic rod, an inflatable anchorage device, and a recovery device. Fifteen field uplift tests are conducted to investigate the effects of inflation pressure, thickness of the steel disc, embedment length, and time lapse between anchor inflation and pullout on “the uplift bearing capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Gong Xiaonan et al [15] elaborated on the commonly used recycling mechanism of recyclable anchor rods based on the application status of recyclable anchor rod technology and provided suggestions on its research and development direction. Du Chenchen et al [16] conducted a pull-out test on the new recyclable anchor rod and revealed the distribution law of the surrounding soil's tensile stress in the pulling-out process of the recyclable anchor rod. Chen Zhibo et al [17] investigated the bearing deformation characteristics of the recyclable anchor rod, suggesting that the bearing characteristics of the recyclable anchor rod were better when the horizontal dip angle of the recyclable anchor rod was between 15 • and 35 • .…”
Section: Introductionmentioning
confidence: 99%
“…Gong Xiaonan et al [15] elaborated on the commonly used recycling mechanism of recyclable anchor rods based on the application status of recyclable anchor rod technology and provided suggestions on its research and development direction. Du Chenchen et al [16] conducted a pull-out test on the new recyclable anchor rod and revealed the distribution law of the surrounding soil's tensile stress in the pulling-out process of the recyclable anchor rod. Chen Zhibo et al [17] investigated the bearing deformation characteristics of the recyclable anchor rod, suggesting that the bearing characteristics of the recyclable anchor rod were better when the horizontal dip angle of the recyclable anchor rod was between 15 • and 35 • .…”
Section: Introductionmentioning
confidence: 99%